Structural, optical and electrical studies on zinc doped barium strontium titanate as photo-anode for DSSC device. (2021) - Kavitha, V.; Mayandi, J.; Mahalingam, P.; Sethupathi, N.
Abstract: Nano crystalline Barium strontium titanate (BST) and zinc doped barium strontium titanate (BSZT) with general formula Ba0.5−x Sr0.5 Znx TiO3 ( x  = 0, 0.05, 0.10 and 0.15) were synthesized by modified sol–gel method. The synthesized nano crystalline powders were characterized using XRD, UV-DRS, FTIR, FESEM, particle size analysis (PSA) and I-V Photovoltaic tests. The structural, optical and electrical properties of the nano crystalline powders were explored. XRD results confirm the formation of cubic structure and their average crystallite size is estimated. The electrical investigation indicates that the addition of Zn to BST nanoparticles improves the conductivity of the sample, hence it could be potential candidate for the solar cells.